2017
DOI: 10.1016/j.neubiorev.2017.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic and ionotropic glutamate receptors as potential targets for the treatment of alcohol use disorder

Abstract: Emerging evidence indicates that dysfunctional glutamate neurotransmission is critical in the initiation and development of alcohol and drug dependence. Alcohol consumption induced downregulation of glutamate transporter 1 (GLT-1) as reported in previous studies from our laboratory. Glutamate is the major excitatory neurotransmitter in the brain, which acts via interactions with several glutamate receptors. Alcohol consumption interferes with the glutamatergic signal transmission by altering the functions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 232 publications
(225 reference statements)
2
59
0
4
Order By: Relevance
“…It has been suggested that the interaction between depression and SUD could lead to glial dysfunction and a consequent alteration in glutamatergic neurotransmission [57, 58], so the pharmacological modulation of this circuit may play a key role in the treatment of SUD in comorbidity with other mental disorders. Ketamine, a glutamate-modulating agent, has been shown to reduce suicide in high-risk populations [58-60], so the inclusion of this medication in the treatment of subjects with SUD with suicidal tendencies is an option that would be worth exploring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the interaction between depression and SUD could lead to glial dysfunction and a consequent alteration in glutamatergic neurotransmission [57, 58], so the pharmacological modulation of this circuit may play a key role in the treatment of SUD in comorbidity with other mental disorders. Ketamine, a glutamate-modulating agent, has been shown to reduce suicide in high-risk populations [58-60], so the inclusion of this medication in the treatment of subjects with SUD with suicidal tendencies is an option that would be worth exploring.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine, a glutamate-modulating agent, has been shown to reduce suicide in high-risk populations [58-60], so the inclusion of this medication in the treatment of subjects with SUD with suicidal tendencies is an option that would be worth exploring.…”
Section: Discussionmentioning
confidence: 99%
“…A prior study from our group reported that upregulating GLT-1 in the NAc and the PFC by ceftriaxone treatment led to an attenuation of EtOH and/or NIC drinking behavior in female P rats (Sari et al, 2016). This indicates that astroglial glutamate transporters, mainly GLT-1, plays a critical role in regulating EtOH or NIC seeking [For review see (Alasmari et al, 2016a, Goodwani et al, 2017]. In the present work, for the first time, we found that peri-adolescent binge-like scheduled access to SUC-NIC downregulated GLT-1 in the NAc compared to water and SUC control groups, while peri-adolescent EtOH-NIC binge-like drinking reduced GLT-1 expression in the NAc compared to the water control and EtOH groups.…”
Section: Accepted Manuscript 17mentioning
confidence: 99%
“…Regarding Group I metabotropic glutamate receptors (mGluRs), mGluR1 is upregulated in animals exposed to EtOH or NIC (Kane et al, 2005. Moreover, it has been shown that mGluR1 antagonists significantly attenuate both EtOH-and NIC-seeking behavior in animals (Dravolina et al, 2007, Besheer et al, 2008, Goodwani et al, 2017 suggesting a potential role for mGluR1 in regulating the reinforcing effects of EtOH and NIC.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In the mammalian central nervous system, NMDARs are primarily comprised of two glutamatesensitive GluN2 subunits, occurring in subtypes GluN2A-D, and two glycine-sensitive GluN1 subunits (Paoletti et al, 2013). Memantine, an NMDAR channel blocker (ie uncompetitive antagonist) with preferential action on GluN2C-or GluN2D-containing NMDARs (Parsons et al, 1999;Kotermanski and Johnson, 2009;Riebe et al, 2016), is clinically used for the treatment of Alzheimer's disease, and has been proposed as a potential treatment option for alcohol use disorders (Goodwani et al, 2017). However, preclinical data indicate that memantine can facilitate aggressive behavior in mice when administered either after acute alcohol intake or during alcohol withdrawal (Newman et al, 2012;Hwa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%